Global income polarization: Relative and absolute perspectives - Vanesa Jordá; Miguel Ni\~no-Zarazúa; Laurence Roope; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper presents the first global and regional estimates of polarization and bipolarization spanning the period 1960-2020. The study relies on group data to implement a flexible parametric model to obtain the global income distribution and polarization estimates. The study introduces a battery of sensitivity tests to assess the reliability of polarization estimates under various assumptions, with particular emphasis on the impact of survey under-coverage of top incomes on global polarization levels and trends. Overall, we find that relative bipolarization has consistently decreased since 1980, while in absolute terms it has increased since 1960. The more general measure of relative polarization has also exhibited a steady decline since 1980; however, the trend in its absolute counterpart depends on the size of a sensitivity parameter, which reflects whether individuals cluster with peers of similar income or are segregated from different income groups. Consequently, absolute polarization declined over time for lower values of this parameter but increased for higher values.
Keywords: D63; C15; C46; 330; global income distribution; bipolarization; polarization